CLINICAL AND ETIOLOGICAL CHARACTERISTICS OF ACUTE RESPIRATORY VIRAL INFECTIONS IN HOSPITALIZED CHILDREN OF THE CITY OF KHABAROVSK IN EPIDEMIC SEASONS 2014-2017 - R. A. Gladkikh; V. P. Molochny; L. V. Butakova; O. E. Trotsenko; V. I. Reznik; I. V. Polesko (LLC "Diagnostics and Vaccines", 2018)
The article presents the results of etiological diagnostics of cases of acute respiratory viral infections (ARVI) in children during the epidemic periods of 2014-2017, the material sampling was carried out at the Children's regional clinical hospital named after A.K. Piotrovich. Comparative material on the three seasons: 2014-2015, 2015-2016 and 2016-2017 years. The features of the annual dynamics of the frequency of allocation of various respiratory viruses are revealed. The most numerous group of patients was children first year of life (infants) - 154 (35.6 ± 2.3%). Among the hospitalized children prevailed patients with moderate severity (of 90.9 ± 1.3%). The causative agent was determined in 307 of 432 observed patients (71 ± 2.1%). It is shown that the predominant viral pathogen in all seasons is the rhinovirus. Among cases of community-acquired pneumonia the dominant pathogen is respiratory syncytial virus. Bocaviruses, metapneumoviruses and coronaviruses were more often found in the form of association with other viruses. The circulation of the influenza virus was accompanied by a decrease in the attention of other respiratory viruses.